Qualimetric Assessment of Professional Methodological Competencies of Students in Biology Lessons in Advanced International Practices - Raupova Mehrinigor Haydarovna; Izzatova Marjona Narzulla qizi (Scientific Trends, 2024)
This article analyzes advanced international practices in qualimetric assessment of students' professional methodological competencies in biology lessons. Approaches in the education systems of Finland, Singapore, and the USA are comparatively studied. Focus is placed on aspects such as the development of practical skills, technological competencies, and project-based learning. The essence and importance of qualimetric assessment, along with its various forms, are elucidated. Common and distinct features of international practices are analyzed, and the possibilities of adapting them to the Uzbekistan education system are considered. The article provides practical recommendations for developing students' professional methodological competencies.
Keywords: Biology education, professional methodological competencies, qualimetric assessment, Finnish experience, Singaporean experience, US experience, education quality, ICT tools, pedagogical technologies, innovations in education.